PENGARUH SISTEM PERPAJAKAN, PELAYANAN PERPAJAKAN, SANKSI PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR PADA SAMSAT NGANJUK - Julian Noni Andani; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Motor vehicle tax is a tax that contributes greatly to income in autonomous regions in Indonesia, regional taxes are one of the largest sources of tax revenue in regions. The importance of increasing compliance with paying motor vehicle taxes in Indonesia so that there is an increase in tax revenues that will be used for the development of national facilities and infrastructure. The purpose of this study was to determine the taxation system, tax services, tax sanctions and awareness of taxpayers against paying for motorized vehicles at Samsat Nganjuk. The research method used is quantitative research. The sample selection used convenience sampling which was distributed via google form to 100 respondents who are obligated as motor vehicle taxpayers. The data analysis method used is the multiple linear regression analysis of the SPSS26 program with the results of the study showing that the value of R square is 0.549 or 54.9% taxpayer compliance is influenced by the tax system, tax services, tax sanctions and taxpayer awareness, while 45.1% is influenced by other factors outside the model. The results of the t-test show that the variable of the taxation system, tax service, and taxpayer awareness have a positive and significant impact on compliance with paying motorized vehicle taxes at Samsat Nganjuk.Keyword : tax system, tax services, tax sanctions, taxpayer awareness and compliance with paying motorized vehicle taxes